Enzymatic Protein Immobilization on Amino-Functionalized Nanoparticles - Qun Ma; Boqiang He; Guojin Tang; Ran Xie; Peng Zheng (Molecules, 2023)
The immobilization of proteins on nanoparticles has received much attention in recent years. Among different approaches, enzymatic protein immobilization shows unique advantages because of its site-specific connection. OaAEP1 is a recently engineered peptide ligase which can specifically recognize an N-terminal GL residue (NH2–Gly–Leu) and a C-terminal NGL amino acid residue (Asn–Gly–Leu–COOH) and ligates them efficiently. Herein, we report OaAEP1-mediated protein immobilization on synthetic magnetic nanoparticles. Our work showed that OaAEP1 could mediate C-terminal site-specific protein immobilization on the amino-functionalized Fe3O4 nanoparticles. Our work demonstrates a new method for site-specific protein immobilization on nanoparticles.